Binding of rat ribosomal proteins to yeast 5.8S ribosomal ribonucleic acid. - Lee, J C (1982)
5.8 S RNA-protein complexes were prepared using purified yeast 5.8 S RNA and proteins from the large ribosomal subunit of rat liver. Formation of such hybrid complexes, as measured by Millipore filtration, was dependent on protein concentration. Binding of proteins to the RNA could approach saturation. Such complexes were isolated from sucrose density gradient centrifugation and shown to contain proteins L6, L8, L19, L35 and L35a. These proteins were identified by their molecular weights on polyacrylamide gels containing dodecylsulfate and their mobilities on two dimensional polyacrylamide gels.